World Health Organization - Grahame, Deborah A. (Milwaukee, WI : World Almanac, 2003)
Describes the founding, development, and staffing of the World Health Organization, and its focus on immunization, disease prevention, sanitation and nutrition as well as combating disease.
Includes bibliographical references and index.
Keywords: World Health Organization -- History; World Health Organization; World health -- Juvenile literature; Public health -- International cooperation -- Juvenile literature